Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Apotek Kimia Farma X Kecamatan Banjarmasin Timur - Nor Ellisa; Mustaqimah Mustaqimah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Background : The quality of service in the health sector is health service that lead to patient satisfaction. Satisfaction is very important in healt service because it can measure the quality of health services. Objective : The purpose of this study was to observe and identify the level of patient satisfaction with pharmaceutical service at Kimia Farma X Pharmacy, East Banjarmasin District. Methods : This type of research is observational research with descriptive research methods. Descriptive research is research carried out with the aim of making a description or description of a situation objectively with a cross sectional study with a total of 32 respondents. Result : Based on the results of the study, it was found that 11 of the 20 statements submitted to respondents were at the level of satisfaction